Physiological effects of combined NaCl and NaHCO3 stress on the seedlings of two maple species - Xu, Bo; Cao, Lina; Zhang, Zhenxing; Li, Xinyu; Zhao, Xiangyu; Wang, Xinyue; Wang, Yining; Wu, Bingchen; Zhou, Weihua; Lin, Chenlu; Gao, Yufu; Rong, Liping (Frontiers in Plant Science, 2023)
Salt stress impacts growth and physiological processes in trees, and the effects of combined NaCl and NaHCO3 stress on the seedlings of Acer species are understudied. In this study, we designed an experiment to measure physiological characteristics by establishing a range of NaCl and NaHCO3 concentrations (0, 25, 50, 75, and 100 mmol L -1 ) to estimate the compound salt tolerance of Acer ginnala and Acer palmatum. When the concentrations of NaCl and NaHCO3 were 25 mmol L -1 , the leaf water content, relative conductivity, malondialdehyde (MDA) content, proline content, soluble sugar content, and chlorophyll did not change (p > 0.05) in two maple seedlings. At concentrations greater than 50 mmol L -1 , the relative conductivity and MDA content increased, proline and soluble sugars accumulated, and the potential activity of PS II (Fv/Fo), potential photochemical efficiency of PS II (Fv/Fm), PS II actual photochemical efficiency (Yield), and photosynthetic electron transfer efficiency (ETR) decreased (p < 0.05). The superoxide dismutase (SOD) and catalase (CAT) activities showed the same trend of first increasing and then decreasing (p < 0.05). The peroxidase (POD) activity increased only when concentrations of NaCl and NaHCO3were 100 mmol L -1 , while there was no statistical difference between the other treatments and the control. Therefore, the two maple seedlings adjusted their osmotic balance and alleviated oxidative stress by accumulating proline, soluble sugars and increasing CAT and SOD activities. Further analysis showed that both species are salt tolerant and the salt tolerance of Acer ginnala is better than that of Acer palmatum.